The welfare cost of means-testing: pensioner participation in income support - Monica Hernandez; Stephen Pudney; Ruth Hancock (University of Essex, Institute for Social and Economic Research (ISER), 2006)
We estimate parametric and semi-parametric binary choice models of benefit take-up by British pensioners and use a revealed preference argument to infer the cash-equivalent value of disutility arising from stigma or complexity of the claims process. These implicit costs turn out to be relatively small, averaging about 3-4 per week across Income Support recipients. Using the Foster-Greer-Thorbecke measure of poverty among pensioners, we find that allowing for implicit claim costs incurred by benefit recipients raises the measured degree of poverty by not more than 13%.
Keywords: 330